Developing a Framework for Improving the Quality of Cost Estimates - Lavdas, Evaggelos (Cranfield University, 2008)
Cost estimating is a knowledge intensive task, involving a high degree of subjectivity. Consequently, many of the current cost estimating (CE) processes lack formalisation, often resulting in the branding of cost estimating as a “part art, part science” discipline. This thesis is concerned with understanding the factors that influence the quality of the cost estimating process. The aim is to develop a framework that will improve the perceived quality of cost estimates, by minimising the subjectivity involved the current CE process. A literature review examines the shortcomings of the current CE processes. It was identified that there is a lack of methodologies for eliciting CE knowledge, as well as mixed views across authors regarding the CE knowledge requirements. In addition, the review identifies that the current methods for assessing the quality of cost estimates are unstructured and highly subjective. By adopting a case study approach, the current CE processes across a number of organisations were captured, resulting in the identification of their weaknesses. A detailed study was carried out regarding the knowledge associated with the cost estimation of complex mechanical hardware products. This led to the development of a Knowledge Elicitation (KEL) methodology, tailored to the needs of cost estimators. Through the use of a survey study, it was identified that the quality of a cost estimate is dependent on the fulfilment of a number of inherent characteristics. It was demonstrated that there was some variation in the relative contribution of each characteristic influencing the overall quality of the estimating process. These findings were implemented in a prototype software tool, which cost estimators could use to assess and quantify the quality of their estimates. A framework was developed based on the merge of the prototype tool and the KEL methodology. The framework’s purpose is to aid cost estimators in acquiring all the necessary knowledge for developing cost estimates of good quality. Novice cost estimators will find the application of the framework particularly beneficial, since they lack the experience and knowledge in a particular domain. In conclusion, it was demonstrated through the case studies that the use of the proposed framework provides novice cost estimators with a formalised process for developing cost estimates of quality similar to the one of experts. The framework was applied on case studies within the aerospace and automotive industry, and their results were validated by experts within the collaborating organisations. As a result of this study’s findings, key areas for future research were identified. The adoption of this approach by cost practitioners could provide increased credibility to their work and a higher level of confidence in their cost estimates.